Przyjaźń w cieniu śmierci. O prozie Thomasa Bernharda - Barełkowska, Agata (Poznańskie Studia Polonistyczne. Seria Literacka, 2010)
The bond of friendship becomes in a number of novels by Thomas Bernhard increasingly important and one of the planes or realms of existence, more often than not inescapably related to some kind of an entanglement, and almost the most precious relation in one’s life — at least one of the most important frames of reference. The chronological order of the texts in which friendship plays a significant role is as follows: Korrektur (Correction, 1975), Wittgenstein’s Nephew (1982), The Loser (1983), Holzfaellen (Cutting Timber, 1984), Extinction (1986). The novelistic worlds created in Extinction and Holzfaellen could not have existed without friendship. However, in Bernhard’s discussion on friendship, the most interesting moments happen when it becomes not only a sanctuary or grievance, but rather when provides inspiration for new escapades of the mind and is an equivocal force (however miraculous and containing traces of genius and madness) portraying vague relationships that sometimes almost cross the border of friendship. Additionally, particular strains carrying the stigma of absence of a friend, so distinctive for the whole of the literary output of Bernhard, are notable — the author usually writes about friendship from within the perspective of death or, as in the case of Wittgenstein’s Nephew, from the perspective of dying.